2000
DOI: 10.1046/j.1432-1327.2000.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of alkaline phosphatases in human breast cancer MCF‐7 cells

Abstract: The effect of retinoic acid and dexamethasone on alkaline phosphatase (AP) expression was investigated in human breast cancer MCF-7 cells. Cellular AP activity was induced significantly by retinoic acid or dexamethasone in a time-dependent and dose-dependent fashion. A marked synergistic induction of AP activity was observed when the cells were incubated with both agents simultaneously. Two AP isozymes, tissuenonspecific (TNAP) and intestinal (IAP), were shown to be expressed in MCF-7 cells as confirmed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 63 publications
(86 reference statements)
0
31
1
Order By: Relevance
“…Although abundantly present in tissues, the regulation of alkaline phosphatase expression changes due to different factors according to cell type. 24,42,43 It has to be noted that PSI-ALA-Hex upon activation gives rise to the production of formaldehyde. Although participating in fundamental biological pathways in cells, the excessive amounts of formaldehyde have toxic effects by inhibiting cell proliferation and leading to apoptosis through the upregulation of tumor suppressor genes p53 and p21 responsible for the cell cycle regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although abundantly present in tissues, the regulation of alkaline phosphatase expression changes due to different factors according to cell type. 24,42,43 It has to be noted that PSI-ALA-Hex upon activation gives rise to the production of formaldehyde. Although participating in fundamental biological pathways in cells, the excessive amounts of formaldehyde have toxic effects by inhibiting cell proliferation and leading to apoptosis through the upregulation of tumor suppressor genes p53 and p21 responsible for the cell cycle regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Agonists of glucocorticoid receptor (GR), such as dexamethasone (Dex) and hydrocortisone, synergistically increase expression of genes induced by tRA (Medh & Schmidt, 1997; Tsai et al, 2000), including NIS (Dohan et al, 2006; Kogai et al, 2005; Unterholzner et al, 2006). Dex significantly increases iodide uptake (>3-fold with 10 −7 M tRA) in MCF-7 cells both in the presence and absence of tRA (Kogai et al, 2005).…”
Section: Nis Regulation By Retinoic Acid In Breast Cancer Cellsmentioning
confidence: 99%
“…Studies have shown that the antitumour effects of ATRA on colon cancer and osteosarcoma are associated with the activity of ALP 1,10 . Using human breast cancer MCF-7 cells as a model, TSAI et al 26 found that cellular ALP activity was significantly induced by retinoic acid in a time-dependent and dose-dependent fashion. In human head-and-neck tumour cells, the ALP activity is very low 4 .…”
mentioning
confidence: 99%